Vulnerabilities of the Communication System to an Electromagnetic (EM) Attack, Threat Assessment and Mitigation (The Shivapuri Journal, 2025)
The rise of electromagnetic (EM) technology has introduced a significant security challenges, particularly for military operations. Opponents regularly try to exploit EM weaknesses to disrupt communications and other weapon systems either physically or remotely. A recent example is the Lebanese Hezbollah’s pager and radio explosion incident where communication system had been weaponized by the adversary attracting worldwide attention in which remotely controlled EM technique was used and thereby presenting a grave concern to all electronic equipment users around the world including Nepal and its security agencies. In Nepalese context, security forces are facing the challenges of lacking reliable modern quality based electronic communication system due to various reasons including budget constraints, limited awareness, meager technological advancements like inadequate EM shielding and so on. As a future strategist and reliable successful military commander, we should visualize another spectrum of our signal vulnerability by EM attacks in our communication system. We need to understand the consequences that could disrupt not only command structure and jeopardize troop safety but also undermine operational effectiveness.